2020
DOI: 10.1016/j.psj.2019.10.058
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of ethanol and thiamine dilaurylsulfate against loosely, intermediately, and tightly attached mesophilic aerobic bacteria, coliforms, and Salmonella Typhimurium in chicken skin

Abstract: The effects of 3 ethanol levels (30, 50, and 70%) with and without thiamine dilaurylsulfate ( TDS ; 1,000 ppm) were evaluated for the reduction of natural mesophilic aerobic bacteria ( MAB ), coliforms, and inoculated Salmonella Typhimurium ( S. Typhimurium) in chicken skin. The chicken skin was inoculated with a 7 log cfu/mL suspension of S. Typhimurium. Loosely, intermediately, and tightly attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Based on the previous experiments, it has been shown that when the initial stress of the prestressed steel wire was less than 0.5 times the value of the ultimate tensile strength Ry, the influence of the relaxation of the steel wire could be ignored [37][38][39][40][41][42]. The maximum initial prestress applied to the steel wire in this test was 0.3Ry (0.3Ry < 0.5Ry).…”
Section: Stress Variation Law Of Prestressed Steel Wirementioning
confidence: 83%
“…Based on the previous experiments, it has been shown that when the initial stress of the prestressed steel wire was less than 0.5 times the value of the ultimate tensile strength Ry, the influence of the relaxation of the steel wire could be ignored [37][38][39][40][41][42]. The maximum initial prestress applied to the steel wire in this test was 0.3Ry (0.3Ry < 0.5Ry).…”
Section: Stress Variation Law Of Prestressed Steel Wirementioning
confidence: 83%
“…Besides, our test on MOL’s sanitiser potential revealed that no microbes were present on the Petrifilms upon combination with 70% ethanol. This was probably due to ethanol’s ability to freely enter microbes’ membranes and inhibit cross-linking of peptidoglycans ( Seo et al, 2020 ). More importantly, these results showed that the combination of MOL with ME and AE preparations in ethanol solutions does not compromise the efficacy of ethanol in microbial reduction.…”
Section: Discussionmentioning
confidence: 99%
“…In this test, the stress variation of the steel bars was caused by two factors, one was the relaxation of the steel bars, and the other was the creep characteristic of the glulam. Previous studies showed that the relaxation of the steel bars was not significant anymore when the initial stress of the prestressed steel bars was less than 0.5 times value of the ultimate tensile strength R y [26][27][28][29][30][31][32][33]. Since the maximum prestress applied in this study was 60 MPa < 0.5fu = 270 MPa, the stress variation caused by the relaxation of the steel bars was ignored, and it was considered that the stress variation of the steel bars was mainly caused by the creep of the glulam.…”
Section: Stress Variation Of Steel Barsmentioning
confidence: 99%